Sistem Pemantauan Kualitas Air Mineral Berbasis Internet of Things - Listiani, Rizka; Syifa, Fikra Titan; Kurnianto, Danny (Teknik Elektro Politeknik Negeri Padang, 2024)
Research has been carried out regarding checking and monitoring water quality based on parameters of turbidity level and dissolved solids in the water. The aim of this research is to rank water quality based on turbidity parameters and dissolved solids in well water, spring water and packaged product water using the simple additive weighting method. The method used is to design a water quality monitoring system using a turbidity sensor and a TDS (total dissolved solid) sensor. Processing data from sensors uses a microcontroller, namely NodeMCU ESP8266. Water quality ranking is carried out using a simple additive weighting method. The results of water quality testing are displayed on the LCD and the Blynk application using Internet of Things technology. The ranking results show that water sourced from springs is of better quality compared to well water. The water quality ranking for packaged products is ranked first, namely product Y, followed by second rank, namely product X, and finally product Z.